2022
DOI: 10.3389/fpubh.2022.991994
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary game-theoretic analysis of construction workers' unsafe behavior: Considering incentive and risk loss

Abstract: The behavior of construction workers has a significant impact on the overall safety climate of a project. The purpose of this paper is to figure out the evolutionary pattern of workers' unsafe behavior and to minimize its occurrence. We constructed a two-sided evolutionary game model consisting of workers and managers to explore the focal point of interest, strategy equilibrium conditions, and behavior evolution process. The experimental results of stability analysis and system dynamics show that there are two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Industrialised buildings also require an efficient and smooth construction process, as all prefabricated components need to be installed within a predetermined time and sequence; any delay can affect the progress and quality of the entire project. This calls for workers to possess professional knowledge and practical experience, to better understand and execute the construction plan, and improve construction efficiency [21]. Technically proficient workers can identify and solve problems during the construction process in a timely manner, avoiding delays and conflicts that could potentially lead to accidents.…”
Section: Resultsmentioning
confidence: 99%
“…Industrialised buildings also require an efficient and smooth construction process, as all prefabricated components need to be installed within a predetermined time and sequence; any delay can affect the progress and quality of the entire project. This calls for workers to possess professional knowledge and practical experience, to better understand and execute the construction plan, and improve construction efficiency [21]. Technically proficient workers can identify and solve problems during the construction process in a timely manner, avoiding delays and conflicts that could potentially lead to accidents.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the evolutionary game approach has also been widely adopted in the study of complex interactions among players. To study the evolutionary pattern of construction workers' unsafe behaviors during construction, Huang et al 38 constructed a two-sided evolutionary game model of construction workers and managers. The results showed that both higher bonuses and higher fines could reduce workers' willingness to choose unsafe behaviors.To study the problem of organizational coordination in sustainable humanitarian supply chains, Zhang et al 39 constructed an evolutionary game model considering traditional mechanism and trust mechanism, and simulated the model using hypothetical data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The construction industry, however, is not recognized as being safe, arguably due to the harsh working environment and the complex and dynamic nature of the work. In the United States, less than 4% of the workforce are in the construction industry, but this accounts for roughly 20% of all fatalities [1,2]. In the U.K., the construction sector accounts for 30% of the fatalities in reported cases [3].…”
Section: Introduction 1backgroundmentioning
confidence: 99%